Peran Rasio Analisis Bisnis Perusahaan Terhadap Harga Saham - Atina Amaliana; Rizka Ariyanti (Jurnal Akuntansi dan Audit Syariah)
This research aims to determine the influence of Return On Equity, Earning Per Share, Net Profit Margin and Price to Book Value on share prices in the food and beverage company sector listed on the IDX for the 2019-2023 period. The research population is food and beverage companies registered on the IDX for 2019-2023. The sampling technique used in this research was purposive sampling. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX). The data analysis method used is multiple linear regression using SPSS version 25. The partial research results show that Return On Equity (ROE) has a negative and significant effect on stock prices, Earning Per Share (EPS) has a positive and significant impact on stock prices, Net Profit Margin (NPM) does not have a positive and significant effect on stock prices and Price to Book Value (PBV) has a positive and significant effect on stock prices. Meanwhile, the results simultaneously show that Return On Equity (ROE), Earning Per Share (EPS), Net Profit Margin (NPM), and Price to Book Value (PBV) have a positive and significant effect on stock prices.